Surface‐Mediated Priming During In Vitro Generation of Monocyte‐Derived Dendritic Cells. (January 2015) - Sauter, A.; Mc Duffie, Y.; Boehm, H.; Martinez, A.; Spatz, J. P.; Appel, S.
Abstract Ex vivo‐generated human dendritic cells (DC) are most commonly generated from monocytes using standard cell culture dishes. To elucidate the effect of the plastic surface during the differentiation process, we compared a standard adhesive plastic dish with four different mainly non‐adherent surfaces. Untouched monocytes were cultured for 3 days in the presence of IL‐4 and GM‐CSF. Time‐lapse videos were recorded, and the phenotype of the cells was analysed by flow cytometry. The cytokine profiles were analysed using a 25‐plex cytokine assay. The use of non‐adherent surfaces led to a significant reduction in expression of CD14 and CD38, and a significant increase in expression of CD86 compared to standard culture dishes. Expression levels of DC‐SIGN and PD‐L2 were reduced significantly on cells cultured on non‐adherent surfaces. The cytokine production was independent on the surface used. The surface‐mediated priming should therefore be considered when aiming to induce specific immune responses. This is especially important with regard to DC‐based immunotherapy, where an adjustment of the surface during the DC generation process might have highly beneficial effects.